Role of peritoneal drainage in moribund patients of perforation peritonitis - Jaiswal, Sakshi; Sharma, Subhash Chandra (International Surgery Journal, 2020)
Background: Objective of the present study was to evaluate applicability of primary peritoneal drainage under local anesthesia in moribund patients as pre-laparotomy support when laparotomy under general anesthesia could not be done. Also to assess outcome in terms of survival, patients needing definitive surgery and complications associated with the procedure on immediate and follow up basis. Methods: We conducted this study in Teerthanker Mahaveer Medical College, Moradabad, UP, India from October 18 to October 2019. 71 patients were admitted as cases of perforation peritonitis in moribund condition, demographic data of all patients was noted, peritoneal drainage under local anesthesia in flanks was done and variable amount of fluid was drained in different patients, simple parameters were taken in to consideration in pre and post drainage phase. We also noted the complications after the definitive surgery. Results: Out of 71 patients, admitted in late and in very critical state, 61 patients improved after drainage and resuscitative procedures, although in ASA grade 3 and 4 they underwent surgical treatment and we were able to save their lives. 13 patients expired after definitive surgery inspite of best efforts. Conclusions: Peritoneal drainage under local anesthesia in late reporting and critical patients, not only improves general condition but makes patients better to undergo further surgery, and can prove to be life saver. It being a simple procedure can easily be done at even PHC level, before patient is referred or shifted to higher centre for further management.